A Hyper-IgM Syndrome Mutation in Activation-Induced Cytidine Deaminase Disrupts G-Quadruplex Binding and Genome-wide Chromatin Localization - Yewdell, William T.; Kim, Youngjun; Chowdhury, Priyanka; Lau, Colleen M.; Smolkin, Ryan M.; Belcheva, Kalina T.; Fernandez, Keith C.; Cols, Montserrat; Yen, Wei-Feng; Vaidyanathan, Bharat; Angeletti, Davide; McDermott, Adrian B.; et al. (Immunity (Cambridge, Mass.), 2020)
Precise targeting of activation-induced cytidine deaminase (AID) to immunoglobulin (Ig) loci promotes antibody class switch recombination (CSR) and somatic hypermutation (SHM), whereas AID targeting of non-Ig loci can generate oncogenic DNA lesions. Here, we examined the contribution of G-quadruplex (G4) nucleic acid structures to AID targeting in vivo. Mice bearing a mutation in Aicda (AIDG133V) that disrupts AID-G4 binding modeled the pathology of hyper-IgM syndrome patients with an orthologous mutation, lacked CSR and SHM, and had broad defects in genome-wide AIDG133V chromatin localization. Genome-wide analyses also revealed that wild-type AID localized to MHCII genes, and AID expression correlated with decreased MHCII expression in germinal center B cells and diffuse large B cell lymphoma. Our findings indicate a crucial role for G4 binding in AID targeting and suggest that AID activity may extend beyond Ig loci to regulate the expression of genes relevant to the physiology and pathology of activated B cells. [Display omitted] •AIDG133V mice lack CSR and SHM and model the pathology of hyper-IgM syndrome•AIDG133V does not bind G4 nucleic acids but is catalytically active•AIDG133V has impaired chromatin localization, but enforced DNA targeting rescues CSR•AID localizes to MHCII genes, and its activity may regulate MHCII gene expression Yewdell et al. examine the contribution of G-quadruplex (G4) nucleic acid structures to AID targeting in vivo using mice bearing a mutation in Aicda found in hyper-IgM syndrome patients. Their findings reveal a crucial role for G4 binding in AID targeting and suggest that AID activity may extend beyond Ig loci to regulate the expression of genes relevant to B cell function.